The Students’ Perception on the Implementation of Computational Thinking in Maritime English Reading Comprehension - Puji Astuti Amalia; Fabiola Bulimasena Luturmas; Sektalonir Oscarini Wati Bhakti; Andri Kurniawan; Setya Ariani; Rizky Sulvika Pusparinda (Poltanesa, 2025)
The implementation of Computational Thinking (CT) in language instruction has drawn interest due to its potential in improving students' analytical and problem-solving abilities. However, its uses in specific fields, such Maritime English especially in reading comprehension, is still not well established. This study is a qualitative study that aims to explore how students perceive the use of CT in Maritime English reading instruction. 31 Students from a maritime higher education institution participated in semi-structured interviews. The result indicates that students view CT as a useful technique for enhancing reading comprehension and engagement. Moreover, the perception is divided into abstraction, algorithm, decomposition, evaluation and pattern recognition. In terms of abstraction, students claim that they can ignore irrelevant information and pick relevant information. In terms of algorithm, students believe that they can apply strategies in reading to make a better comprehension such as underline keywords. In terms of decomposition, students feel confident in breaking down long and complex sentences to find the meaning. In terms of evaluation, students can evaluate the information in the text. In terms of pattern recognition, students are aware of common pattern/sentence structure and organization in the text. The study emphasizes the value of contextualized CT education and offers suggestions for integrating CT into Maritime English learning reading instruction. The finding of this study offers potential instructional strategies for maritime education.